Introduction to the special issue on movement science for humans and humanoids - Kulic, Dana; Venture, Gentiane; Yamane, Katsu; Demircan, Emel; Mombaur, Katja (IEEE transactions on robotics, 2016)
The thirteen papers in this special section focus on the topic of movement science for humans and humanoids. The papers include the collection and organization of human movement data for enabling robotics research; the use of human movement as inspiration for humanoid planning, control, and motion generation; the development of algorithms for improved estimation of human and humanoid system parameters; and the use of human movement understanding in robotics applications including human-robot interaction and rehabilitation.
Gesehen am 03.06.2020